2020
DOI: 10.7759/cureus.7488
|View full text |Cite
|
Sign up to set email alerts
|

Improved Functional Outcomes Following Operative Treatment of Midshaft Clavicle Fractures in an Active Duty Population

Abstract: Clavicle fractures are common orthopedic injuries that occur in a young active population and are even more common in the military. Military fitness test data presents the unique opportunity to analyze functional ability with regard to military-specific activities. The primary goal of this study was to compare functional outcomes using military fitness test data between operative and non-operative treatment of midshaft clavicle fractures. We performed a retrospective review of active-duty U.S. Navy and Marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The prevalence of Robinson type 2B1 and type 2B2 was 45% and 55% respectively whereas, in one of the studies, the prevalence was 27.9% and 15.2% respectively.6 Our study showed excellent functional outcomes in 82.50% of cases and no cases of nonunion or malunion which was similar to the results shown by studies. 4,[17][18][19] In our study, the mean age of the patients was 31.45±4.97 years. This finding was similar to various similar studies suggesting the higher prevalence of clavicular fractures in young and active populations.…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence of Robinson type 2B1 and type 2B2 was 45% and 55% respectively whereas, in one of the studies, the prevalence was 27.9% and 15.2% respectively.6 Our study showed excellent functional outcomes in 82.50% of cases and no cases of nonunion or malunion which was similar to the results shown by studies. 4,[17][18][19] In our study, the mean age of the patients was 31.45±4.97 years. This finding was similar to various similar studies suggesting the higher prevalence of clavicular fractures in young and active populations.…”
Section: Discussionmentioning
confidence: 57%
“…Numerous previous studies have used FE analysis to gain a better understanding of the disease consequences in terms of timing, outcomes, and healthcare costs [35,[42][43][44]. Several authors have demonstrated improved early functional outcomes with lower rates of nonunion and symptomatic aesthetic deformity with surgical treatment of clavicle fractures compared to non-surgical treatment [45,46]. The decision between surgical and non-surgical treatment should be based on several factors, such as the severity of the injury, the occurrence of complications, the patient's age, and the activity level [14].…”
Section: Discussionmentioning
confidence: 99%
“…14 In patients with highly physical jobs (e.g. active military personnel or sportsmen) or those with active lifestyles, surgery can be offered to improve functional outcomes, as suggested by Lake et al 32 Shortening on its own is not an indication for surgery, in accordance with the evidence presented by Goudie et al 51 and Malik et al 52 In line with the management strategy developed by Nicholson et al, 42 all patients should be reassessed at six weeks for the following criteria. If they have two of the following three features -a QuickDASH score greater than 40, no callus on radiograph, and movement at the fracture site -they should be advised that there is a 60% chance of progressing to a nonunion, and operative intervention should be considered.…”
Section: Discussionmentioning
confidence: 99%
“… 14 In patients with highly physical jobs (e.g. active military personnel or sportsmen) or those with active lifestyles, surgery can be offered to improve functional outcomes, as suggested by Lake et al 32 …”
Section: Discussionmentioning
confidence: 99%